2004
DOI: 10.1359/jbmr.040132
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Bone Mineral Density: Evidence for a Major Pleiotropic Effect From an Intercontinental Study

Abstract: BMD is a primary predictor of osteoporotic fracture, and its genetic determination is still unclear. This study showed that the correlation between BMD at different skeletal sites is caused by an underlying genetic structure of common genetic effects. In addition to possible shared (pleiotropic) genetic and environmental effects, each of the BMD variables may also be determined by site-specific genetic factors.Introduction: BMD is a primary predictor of osteoporotic fracture and a key phenotype for the genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 29 publications
1
30
3
Order By: Relevance
“…Bivariate linkage analysis has been shown to have increased power over univariate analysis in detecting genes of pleiotropic effect. 16 A significant pleiotropic effect on LS and FN BMD was estimated in a large sample from an intercontinental study, 28 and our own quantitative analysis showed that the genetic correlations at all three pairs of skeletal sites are significantly different from 0 (Table 1). Others 10,29 have used principal component analysis to test for common QTLs underlying bone mass at different skeletal sites.…”
Section: Discussionmentioning
confidence: 92%
“…Bivariate linkage analysis has been shown to have increased power over univariate analysis in detecting genes of pleiotropic effect. 16 A significant pleiotropic effect on LS and FN BMD was estimated in a large sample from an intercontinental study, 28 and our own quantitative analysis showed that the genetic correlations at all three pairs of skeletal sites are significantly different from 0 (Table 1). Others 10,29 have used principal component analysis to test for common QTLs underlying bone mass at different skeletal sites.…”
Section: Discussionmentioning
confidence: 92%
“…The association of different haplotypes with different skeletal sites, and also the observation of an opposite effect in pre-and post-menopausal women suggest that the effect of ALOX15 is site dependent and menopausal-status dependent [2] . This finding supports that of our recent study wherein the linkage of quantitative trait locus with BMD variation was site-specific and menopause status-specific [28] .…”
Section: Discussionmentioning
confidence: 99%
“…Among the various parameters that contribute to bone strength, bone mineral density (BMD) is one of the best predictors of fracture risk and the most well described. Numerous twin and family studies suggest that BMD, bone mineral content (BMC) and bone area are to a great extent genetically determined [1][2][3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…As a strong (B0.5) and positive phenotypic covariation exists for BMD values at the LS and at the FN, 23 we generated data for two positively correlated quantitative phenotypes. Further, in real data sets, as causal loci usually contribute a small proportion to the total phenotypic correlation, residual correlation approximates phenotypic correlation between traits.…”
Section: Simulation Studymentioning
confidence: 99%